A green sorbent for CO2 capture: α-cyclodextrin-based carbonate in DMSO solution. Issue 66 (9th November 2018) - Eftaiha, Ala'a F.; Qaroush, Abdussalam K.; Alsoubani, Fatima; Pehl, Thomas M.; Troll, Carsten; Rieger, Bernhard; Al-Maythalony, Bassem A.; Assaf, Khaleel I.
Abstract : α-Cyclodextrin dissolved in DMSO is a potential sorbent for CO2 capture through the exclusive formation of ionic organic carbonate. Abstract : Cyclodextrin (α-CD)/KOH pellet dissolved in DMSO was utilized to capture CO2 . KOH has a dual function of enhancing the nucleophilicity of the hydroxyl groups on the α-CD rims and acting as a desiccant. 13 C NMR spectroscopy provided evidence for the chemisorption of CO2 through the formation of organic carbonate (RO-CO2 − ·K + ). This was supported by the spectral changes obtained using ex situ ATR-FTIR spectroscopy upon bubbling CO2 . Activation of α-CD with NaH or bubbling with 13 CO2 verified that chemisorption occurred solely via RO-CO2 − ·K + rather than inorganic bicarbonate. Volumetric gas uptake demonstrated a sorption capacity of 21.3 wt% (4.84 mmol g −1 ). To the best of our knowledge, this is the highest chemisorption value reported to date for CD-based sorbents. DFT calculations of the Gibbs free energies indicated that the formation of RO-CO2 − ·K + was more favoured at the primary carbinol rather than its secondary counterpart.